Ultrastructure of bovine sperm chromatin. Issue 12 (30th October 2015) - Filho, Romualdo Morandi; Beletti, Marcelo Emilio; de Oliveira, Fabio
ABSTRACT: Mammalian semen chromatin comprises DNA, protamine, and, at lower levels, other proteins. This constitution confers intense compaction to the chromatin, helping to protect the DNA and causing the head of the sperm to be very small, facilitating the safe transport of its genetic contents. It is known that changes in the sperm chromatin compaction lead to fertility problems in bulls, justifying studies of this structure. Although there are theoretical models of sperm chromatin because of its high compaction, there is no morphological evidence of such models. The aim of this study was to demonstrate the ultrastructure of bovine sperm chromatin in an attempt to corroborate the theoretical chromatin models existing today. The isolated bull sperm heads had their chromatin partially unpacked by chemical treatment using sodium dodecyl sulfate (SDS) and dithiothreitol (DTT) and were then embedded in Epon resin. Using an ultramicrotome, ultrathin sections were obtained, which were contrasted with uranyl acetate and lead citrate, and then viewed under transmission electron microscopy. The methodology used allowed the visualization of toroidal structures interconnected by a filamentous nuclear matrix, which is entirely consistent with the most current theoretical models. Microsc. Res. Tech. 78:1117–1120, 2015 . © 2015 Wiley Periodicals, Inc.